Association of Colletotrichum acutatum with fruit rot of capsicum in North western Himalayas and identification of resistant sources - PREM NATH SHARMA, ABHISHEK KATOCH* and (Indian Phytopathology, 2015)
The studies were undertaken to identify the pathogen associated with fruit rot of capsicum and their resistance sources in North-western Himalayas. The Colletotrichum species showing incidence up to 50.0% and severity index of 30.5% in chili fields was identified as C. acutatum based on morphological characteristics as well as species-specific DNA markers. The pathogen was further subcategorized as C. simmondsii within the phylogeny of C. acutatum complex using two DNA barcode markers, internal transcribe spacer region (ITS) and Î²-tubulin (TUB2) gene sequence data. Five capsicum accessions namely, EC631750, EC631751, California Wonder, PBC 80 and PBC 81 were identified as potential resistance donors while screening 195 germplasm lines against this species.